Study of Vanadium Doped ZnO Films Prepared by dc Reactive Magnetron Sputtering at Different Substrate Temperatures - Meng, Lijian (2014)
ZnO films doped with vanadium (ZnO:V) have been prepared by dc reactive magnetron sputtering technique at different substrate temperatures (RT–500 C). The effects of the substrate temperature on ZnO:V films properties have been studied. XRD measurements show that only ZnO polycrystalline structure has been obtained, no V2O5 or VO2 crystal phase can be observed. It has been found that the film prepared at low substrate temperature has a preferred orientation along the (002) direction. As the substrate temperature is increased, the (002) peak intensity decreases. When the substrate temperature reaches the 500 C, the film shows a random orientation. SEM measurements show a clear formation of the nano-grains in the sample surface when the substrate temperature is higher than 400 C. The optical properties of the films have been studied by measuring the specular transmittance. The refractive index has been calculated by fitting the transmittance spectra using OJL model combined with harmonic oscillator.